The myth of artificial intelligence : why computers can't think the way we do - Larson, Erik J. (Erik John) (The Belknap Press of Harvard University Press, 2021)
"Futurists are certain that humanlike AI is on the horizon, but in fact engineers have no idea how to program human reasoning. AI reasons from statistical correlations across data sets, while common sense is based heavily on conjecture. Erik Larson argues that hyping existing methods will only hold us back from developing truly humanlike AI"--